1987
DOI: 10.1016/s0886-3350(87)80102-5
|View full text |Cite
|
Sign up to set email alerts
|

Modern intraocular lens implants in children with new age limitations

Abstract: Seventy-three children received modern designs of posterior and flexible anterior chamber intraocular lenses. Twenty-eight (38%) had anterior chamber and 45 (62%) had posterior chamber lenses implanted. Postoperative implant complications occurred in 38 (54%) eyes; the most frequent was secondary membrane formation. Six eyes (22%) with anterior chamber lenses and 25 eyes (58%) with posterior chamber lenses required posterior capsulotomies. Seventy percent of the posterior chamber lens recipients less than six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Children with traumatic or complicated cataracts and those who underwent cataract extraction without PPC or AV were excluded. As the risk of developing postoperative complications is commoner in younger children, [5][6][7][8][9] we divided all the children into less and more than 2 years. As implantation of IOL can further influence intraoperative difficulties and postoperative complications like VAO, the children less than 2 years were further divided on the basis of IOL implantation.…”
Section: Methodsmentioning
confidence: 99%
“…Children with traumatic or complicated cataracts and those who underwent cataract extraction without PPC or AV were excluded. As the risk of developing postoperative complications is commoner in younger children, [5][6][7][8][9] we divided all the children into less and more than 2 years. As implantation of IOL can further influence intraoperative difficulties and postoperative complications like VAO, the children less than 2 years were further divided on the basis of IOL implantation.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18][19][20] The change in refraction seen over the first two years or so of a child's life-usually a loss of several dioptres of hypermetropia-have suggested to some that an intra ocular lens might need replacement at least once in a life time to keep up with this change; full correction from the start would lead to marked overcorrection later.8 Also, although there is now forty years' experience with PMMA as an intraocular material, this is perhaps only half a child's expected lifetime, and PMMA itself is probably not the most suitable lens material for an infant's eye, because a rigid lens may be more difficult to introduce and could damage corneal endothelial cells by direct contact.…”
mentioning
confidence: 99%
“…Early reports of IOL implantation during childhood emphasized the high complication rate associated with their use. [8][9][10][11][12][13] As a result, some investigators recommended that IOLs be implanted only in older children with unilateral traumatic cataracts or in children who could not tolerate CLs. [8][9]14 Results of many of these early case series also showed that anterior chamber and iris fixation CLs were associated with fewer complications than were posterior chamber IOL implants.…”
Section: Discussionmentioning
confidence: 99%